Neolithic bodies - Bickle, Penny; Sibbesson, Emilie (Neolithic Studies Group seminar papers, 2018)
"This volume, building on the Neolithic Studies Group conference in 2014, captures the variety of debates taking place across research into Neolithic bodies of the Near East and Europe. Papers are divided into three themes: living bodies, the body in death, and representations of the body. Together these themes survey approaches from 'body worlds' and technologies of the body to the myriad of complex social statements consolidated in art and funerary rites"--Page 4 of cover